2019
DOI: 10.1021/acsnano.8b07524
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Quantitative Co-Mapping of Pulmonary Morphology and Nanoparticle Distribution with Cellular Resolution in Nondissected Murine Lungs

Abstract: Deciphering biodistribution, biokinetics and biological effects of nanoparticles (NPs) in entire organs with cellular resolution remains largely elusive due to the lack of effective imaging tools.Here, light sheet fluorescence microscopy in combination with optical tissue clearing was validated for concomitant three-dimensional mapping of lung morphology and NP biodistribution with cellular resolution in non-dissected ex vivo murine lungs. Tissue autofluorescence allowed for label-free, quantitative morphometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 65 publications
(191 reference statements)
4
57
1
Order By: Relevance
“…Lungs from nine independent slow‐instillation experiments were stratified for preferentially left and right as well as uniform (global) NP deposition in the lung. The ratios of the fluorescence intensities from the right and left lung, which are normalized to their respective right and left lung volume to account for the effect of volume‐dependent lung ventilation, reveal that for global delivery the ratio is equal to unity and a 3.7‐fold preferential targeting of the right (3.7) and left (3.7 = 1/0.27) half of the lung was accomplished, respectively (Figure e). Finally, the delivered dose was determined from quantitative fluorescence analysis using dose‐intensity conversion curves based on two reference lungs containing known amounts of polystyrene‐SkyBlue NPs (using regular intratracheal instillation) and three nontreated lungs for tissue‐autofluorescence correction .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lungs from nine independent slow‐instillation experiments were stratified for preferentially left and right as well as uniform (global) NP deposition in the lung. The ratios of the fluorescence intensities from the right and left lung, which are normalized to their respective right and left lung volume to account for the effect of volume‐dependent lung ventilation, reveal that for global delivery the ratio is equal to unity and a 3.7‐fold preferential targeting of the right (3.7) and left (3.7 = 1/0.27) half of the lung was accomplished, respectively (Figure e). Finally, the delivered dose was determined from quantitative fluorescence analysis using dose‐intensity conversion curves based on two reference lungs containing known amounts of polystyrene‐SkyBlue NPs (using regular intratracheal instillation) and three nontreated lungs for tissue‐autofluorescence correction .…”
Section: Resultsmentioning
confidence: 99%
“…While CT scan and LSFI offer 3D imaging capabilities, they do not allow for NP localization within individual cells. We recently demonstrated that ex vivo LSFM allows for quantitative co‐mapping of lung architecture and NP deposition with single‐cell resolution in nondissected but optically cleared lungs . Here we apply this method to study the pulmonary distribution of 100 µL of an NP suspension after intratracheal slow‐instillation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tissue was imaged using a Zeiss Z.1 lightsheet microscope equipped with a 5x/0.16 detection objective. Blood vessels were detected using hemoglobin autofluorescence excited with the 405nm laser line and detected using a 500-545nm GFP band pass filter (24). Multiview data sets were acquired at 120-degree angles and fused using the Multiview Reconstruction plugin in FIJI (25).…”
Section: Methodsmentioning
confidence: 99%